Violência e religiosidade popular em Catalão-GO: a construção da santidade de Antero 1932-2012 - Silva, Jaciely Soares da (2014)
We propose in this work to develop reflections on popular devotion around Antero da Costa Carvalho, former resident of the city of Catalão- GO which in 1930 was killed by being accused of ordering the murder of Albino Felipe do Nascimento, also resident of Catalão. Antero becomes part significantly from the history and memory of Catalão when, after being accused and arrested, was violently killed by gunmen and some popular city . From this central episode in its history begins to be penetrated by the devotional tragic moment, the local population began to assign to Antero supernatural powers, coming to the present as a saint in catalano religious imagery. Thus, we assume that the shape of how his death occurred, associated with other elements such as the image of Antero as good man and context of violent city itself can be seen as significant elements so that it would start a whole devotion and belief around Antero. Our research we rely on theoretical and methodological bases of Cultural History, and as a field of debate concepts related to culture, popular religion, memory and imagination. As a methodological approach, we propose discussions on the concepts of popular culture, sanctity and piety. As empirical material for documentary analysis , we turn to Case Crime Albino Felipe do Nascimento, which recounts in detail the events leading up to the death of Antero; newspapers that currently bring a rereading of the case; fictionalized memoirs books and literature that addresses the case. As field work, we seek to bring to the study oral sources and photographs that reference devotion around Antero and votive brands such as holiness and memory of the saint. Oral sources, in particular, brought to the research narratives and memories in which the story of life and death of Antero has today maintained and propagated from the experienced and shared devotional experience, a large majority for their devotees.